An Analytical Study on the Role of Local Government in the Resolution of Mining Blasting Disputes in Barito Selatan Regency - Ikhsan, Syahrul; Sadiani; Putera, M. Luthfi Setiarno (Universitas Islam Negeri Alauddin Makassar, 2025)
This article examines the role of the Local Government of Barito Selatan Regency in resolving disputes arising from blasting activities conducted by PT. Multi Tambang Jaya Utama. The study aims to assess the significant social and environmental impacts experienced by the surrounding community, which necessitated a prompt response from local authorities. Employing an empirical research method and a socio-legal approach, this study provides an in-depth analysis of the mediation process and dispute resolution strategies undertaken by the local government. The primary challenge encountered is structural, particularly concerning the limited authority of the local government over mining affairs following the enactment of Law No. 23 of 2014, which transferred most natural resource management powers to the central government. Nevertheless, the Local Government of Barito Selatan demonstrated initiative and commitment by establishing the Social Conflict Resolution Team (PKS). This team is tasked with facilitating dialogue between the company and the community, as well as formulating participatory and sustainable resolution measures. The findings indicate that despite limited authority, the active role of the local government remains crucial in maintaining social stability. Therefore, strengthening regulations, institutional support, and enhancing community participation are essential to achieving fair, inclusive, and sustainable dispute resolution.